(untitled) (Canadian Oncology Today, 2024)
Pancreatic ductal adenocarcinoma (PDAC), a cancer of the gastrointestinal tract, has been increasing in incidence, with an estimated doubling worldwide over the past two decades. Despite increases in awareness and innovations in genomics and drug discovery, 5-year survival remains low, at only 10%. This is in part owing to the majority of patients being diagnosed at the advanced stage of the disease, in addition to chemotherapy recalcitrant disease. Surgical resection is necessary for a potential cure, however, this is only possible for the 10% of patients who present with resectable disease and potentially for those with borderline resectable disease. Locally advanced pancreatic cancer accounts for approximately 30% of those with PDAC and most of those patients are often precluded from curative intent surgery due to major vascular invasion and local infiltration into peri-pancreatic soft tissue. In cases of locally advanced disease, induction chemotherapy is often used, identifying the subgroup of patients more suited for local treatments and those who may later develop metastases. The treatment regimens used for patients with locally advanced PDAC are often extrapolated from trials involving patients with metastatic disease. In some cases, responses to neoadjuvant therapy have allowed for surgical resection, albeit these aggressive resections were associated with significant morbidity. There is growing interest in identifying the optimal neoadjuvant treatment for patients with borderline resectable pancreatic cancer (BRPC) and locally advanced PDAC (LAPC) in an effort to improve outcomes. Here we review therapeutic strategies for borderline resectable and locally advanced PDAC, with a focus on novel systemic therapy regimens, chemoradiation, and different radiation modalities.